1995
DOI: 10.1016/0005-2736(95)00138-s
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of antibodies to sterically stabilized liposomes: evaluation, comparison and optimization of coupling procedures

Abstract: Several coupling methods for binding antibodies (Ab) to liposomes have previously been developed. We were interested in examining if some of these methods would be suitable for attaching Ab to long-circulating formulations of liposomes (SL), sterically stabilized with poly(ethylene glycol) (PEG). We studied three 'classical' coupling methods in which Ab was attached at the bilayer surface of SL, and two new coupling methods in which Ab was attached at the PEG terminus. Parameters examined including binding eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(199 citation statements)
references
References 34 publications
4
194
0
1
Order By: Relevance
“…Monoclonal antibody (mAb) 2G4 was produced and purified in our laboratory. Also, pNP-PEG 3400 -PE was synthesized and purified according to an established method in our laboratory (27) Developing the method of coupling oxidized antibody to the PEG terminus through a hydrazone bond as suggested by Hansen et al (28), we devised our own scheme of conjugate reaction for synthesis of pH-cleavable PEG-PE. The reaction was performed in two steps: first, the activation of mPEG 2000 -CHO with PDPH, and second, the conjugation of 1,2-dipalmitoylsn-glycero-3-phosphothioethanol (sodium salt) (PE-SH) to activated mPEG-CHO.…”
Section: Methodsmentioning
confidence: 99%
“…Monoclonal antibody (mAb) 2G4 was produced and purified in our laboratory. Also, pNP-PEG 3400 -PE was synthesized and purified according to an established method in our laboratory (27) Developing the method of coupling oxidized antibody to the PEG terminus through a hydrazone bond as suggested by Hansen et al (28), we devised our own scheme of conjugate reaction for synthesis of pH-cleavable PEG-PE. The reaction was performed in two steps: first, the activation of mPEG 2000 -CHO with PDPH, and second, the conjugation of 1,2-dipalmitoylsn-glycero-3-phosphothioethanol (sodium salt) (PE-SH) to activated mPEG-CHO.…”
Section: Methodsmentioning
confidence: 99%
“…The affinity coupling of IgGs to ZZ domains presents several major advantages; not only it is highly efficient and complete, but it involves un-modified IgGs, avoids possible alteration by chemical modification, and maintains an optimal orientation of IgGs towards their target site [20,21]. In comparison, the covalent coupling of IgGs to lipid hydrazides via carbohydrate residues located in Fc domains constitutes another approach allowing the control of the IgG orientation, yet with low yield [15]. Another advantage of the non-covalent binding of Anx5ZZ to IgGs is that the reaction is complete in near stoichiometric conditions and thus does not require purification procedures, in contrast to most methods of protein derivatization which require an excess of crosslinkers in order to achieve a satisfactory yield, and consequently a purification step for eliminating un-reacted molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The Anx5ZZ fusion protein constitutes therefore a simple, fast and versatile adaptor system for linking IgGs to liposomes, in a plug-and-use fashion. In comparison, several studies have reported variable coupling yields (from 100 to 10%) for the formation of immunoliposomes by covalent conjugation [15,[30][31][32], together with the need of excess lipid reactive groups to reach reasonable coupling rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linking of antibodies to liposomes has been intensely studied from different perspectives (see review (Hansen, Kao et al, 1995)). Most of these techniques have been used in different cellular and animal models.…”
Section: The Immunoliposome Designmentioning
confidence: 99%